Active bimetallic Fe–O–Co sites built on 2D trimetallic complex spinel oxides for industrially oxygen evolution electrocatalyst. (December 2022) - Cheng, Z.; Yang, H.; Xu, Y.; Jiang, J.; Xu, Q.
Abstract: Fabrication of active and durable non-noble metal heterogeneous electrocatalysts to settle the relatively slow kinetic process and poor stability during the oxygen evolution reaction (OER) process is of great significance. Herein, we fabricate in-situ 2D Fe-based trimetallic complex spinel oxide nanosheets (FeCoNi)O4 via a polyethylene glycol-barbituric acid deep eutectic solvent-assisted route. Multiple analytical characterizations illustrate a deep understanding of the structure and composition of (FeCoNi)O4, disclosing Fe, Co, and Ni ions occupy both tetrahedrally and octahedrally coordinated positions. Meanwhile, the synergistic actions of preparing multiple-cations substitution and constructing oxygen vacancy activate covalent Fe–O–Co bonds in (FeCoNi)O4 . Due to the active bimetallic Fe–O–Co sites, enhanced electronic conductivity and unique structure stability, the synthesized 2D (FeCoNi)O4 nanosheets exhibit excellent OER performance with relatively low overpotential (421 mV for 1000 mA/cm 2 ) and long-term stability (720 mA/cm 2 for 6 h) in alkaline media, which is much better than that of Fe-based bi/monometallic spinel oxides. In-situ Raman spectra and quasi-in-situ X-ray photoelectron spectroscopy results depict that O-bridged Fe–O–Co bimetallic sites promote the formation of μ(O–O) intermediates and undergo the direct O2 evolution route, thus accelerating OER. Graphical abstract: Benefitting from the activated covalent Fe–O–Co bond induced by the synergy of multiple cation substitution and proper oxygen vacancies, 2D non-van der Waals trimetallic complex spinel oxide (FeCoNi)O4 nanosheets exhibit excellent activity and long-term stability for OER. Image 1 Highlights: A series of two-dimensional Fe-based spinel oxide nanosheets are controllably synthesized. Multi-metal substitution optimizes the electronic state of 2D (FeCoNi)O4 and enhances the electron transfer between Fe and Co. Metal substitution also facilitates the Fe-O-Co electronic interactions by regulating oxygen vacancy and oxidative state. The in-situ Raman technique probes the mechanism of the excellent performance of oxygen evolution reaction.